2016
DOI: 10.1007/s11356-016-6224-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nutrient removal from municipal wastewater assisted by mixotrophic microalgal cultivation using glycerol

Abstract: In a present study, nutrient removal from municipal wastewater by Chlorella vulgaris and Nannochloropsis oculata was investigated by using mixotrophic cultivation with glycerol (0 to 5 g/L). Performance parameters were assessed by estimating the removal of total nitrogen, total phosphorus, chemical oxygen demand (COD), biomass growth, chlorophyll content, lipid yield, and fatty acids. With the addition of 2 g/L glycerol, a maximum biomass productivity of 56 mg/L/day was achieved in the mixotrophic culture of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…The differences in phosphorus removal among various studies might be due to the uptake of phosphorus by microalgae is affected by algal physiology, initial phosphate concentration, and chemical form of available phosphate, light intensity, pH, and temperature (Gupta et al 2016). Choi and Lee (2014) also shown that removal of TN depends on the N/P ratio, which affects biomass growth and, N and P nutrients removal in wastewater.…”
Section: Phosphorus Removalmentioning
confidence: 99%
“…The differences in phosphorus removal among various studies might be due to the uptake of phosphorus by microalgae is affected by algal physiology, initial phosphate concentration, and chemical form of available phosphate, light intensity, pH, and temperature (Gupta et al 2016). Choi and Lee (2014) also shown that removal of TN depends on the N/P ratio, which affects biomass growth and, N and P nutrients removal in wastewater.…”
Section: Phosphorus Removalmentioning
confidence: 99%
“…Perez-Garcia 115 found the highest growth rate and ammonium uptake of C. vulgaris growing on sterilized municipal wastewater when adding sodium acetate under heterotrophic conditions, while the absence of external carbon supplementation resulted in reduced growth. Gupta et al [49] reported that the addition of glycerol enhanced biomass productivity and nutrient uptake of C. vulgaris and Nannochloropsis oculata, when cultivated on municipal wastewater. Similar results were reported by Ma et al [87] who reported that nutrient uptake and lipid yield was increased when synthetic wastewater was supplemented with waste glycerol.…”
Section: Carbonmentioning
confidence: 99%
“…To optimize wastewater utilization, pretreatment processes of the raw source need to be employed. Several researchers reported that a high turbidity from the wastewater may induce heterotrophic or mixotrophic growth that benefits biomass production, lipid accumulation, and nutrient uptake [5,49]. Furthermore, to provide CO 2 for mixotrophic cultivation, and lowering COD and BOD content in POME, the wastewater could be processed in an anaerobic fermentor, resulting in methane that could be used directly as an energy source.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Crude glycerol can be used as a feedstock for the cultivation of lipid producing microalgae and the lipid produced can then be reused for biodiesel production. Growth and lipid production studies using glycerol as an organic C‐source have been conducted using C. protothecoides, C. vulgaris , S. limacinum, N. oculata , B. braunii , Haematococcus sp ., Nannochloris sp ., and Scenedesmus sp . to demonstrate the potential for recycling crude glycerol generated during biodiesel production in the cultivation process.…”
Section: Waste Streams For Microalgal Cultivationmentioning
confidence: 99%